Isolated Rare Urethral Metastasis From Primary Lung Adenocarcinoma: Case Report and Literature Review - Zhu, Xin; Li, Heqiu; Li, Shuang; Zhou, Mi (Frontiers in Oncology, 2019)
Background: Lung adenocarcinoma is a common respiratory malignancy, however urethral metastasis of lung adenocarcinoma has not yet been reported. This study aims to present a rare case of isolated urethral metastasis in a male patient with a history of primary lung adenocarcinoma. Case presentation: A 69-year-old male patient was admitted complaining of dysuria and nocturia for 3 months, with a history of lung adenocarcinoma after surgery. The patient was diagnosed as benign prostatic hyperplasia (BPH) and received holmium laser enucleation of the prostate, an effective transurethral procedure to treat bladder outflow obstruction due to BPH. Four months after surgery for BPH, the patient had no improvement in symptoms and continued to complain of dysuria and perineum pain. An MRI of the pelvis indicated posterior urethral mass without any regional lymphadenopathy or other sites of lesion. Urethrocystoscopy found the mass in the membranous urethra near the verumontanum, and pathology combined with immunohistochemical staining confirmed the isolated urethral metastasis of lung adenocarcinoma. The further therapeutic regimen consisting of chemotherapy (pemetrexed combined with nedaplatin) and bevacizumab was well tolerated, and obviously relieved the patient from dysuria and perineum pain. Conclusion: This study reported the first case of isolated rare urethral metastasis from primary lung adenocarcinoma and underlined the necessity for clinicians to remain vigilant to metastasis during follow-up of primary cancer.